Energy evaluation of low-level control in UAVs powered by lithium polymer battery. (November 2017) - Gandolfo, Daniel C.; Salinas, Lucio R.; Serrano, Mario E.; Toibero, Juan M.
Abstract: Nowadays, the energetic cost of flying in electric-powered UAVs is one of the key challenges. The continuous evolution of electrical energy storage sources is overcome by the great amount of energy required by the propulsion system. Therefore, the on-board energy is a crucial factor that needs to be further analyzed. In this work, different control strategies applied to a generic UAV propulsion system are considered and a lithium polymer battery dynamic model is included as the propulsion system energy source. Several simulations are carried out for each control strategy, and a quantitative evaluation of the influence of each control law over the actual energy consumed by the propulsion system is reported. This energy, which is delivery by the battery, is next compared against a well-known control-effort-based index. The results and analysis suggest that conclusions regarding energy savings based on control effort signals should be drawn carefully, because they do not directly represent the actual consumed energy. Abstract : Highlights: IFour different control strategies are applied to a generic UAV propulsion system A lithium polymer battery dynamic model is considered as system energy source Two saving scores are used to compare the actual energy savings Controllers are analyzed according to energy savings, control effort and performance Results suggest that conclusions regarding energy savings should be drawn carefully